Émergence de l’entreprise francophone du Québec - Melançon, Jacques (Assurances)

(untitled) (HEC Montréal, 1987)
In 1936, Mr. Victor Barbeau published Mesure de notre taille, which depicted a rather bleak portrait of French Canadian business. In 1956, Mr. Jacques Melançon took up this study from a different perspective - the situation, aside from very few exceptions, had remained virtually unchanged: businesses owned by French Canadian interests were small or medium-sized and skills were limited or not put to good use. The general public did not understand that the future for French Canadians, as regards individual or group ventures, was in their members though, at the time, this seemed to matter only at election time. French Canadians on the boards of major companies were few and far between. As a group, they were very often referred to as the French Canadian serving class. But, things have changed. This is the theme of Mr. Melançon's most interesting update of his 1956 study. We are pleased to present his work which plots the progress made by French Canadians in recent years. Rather than examine the obstacles encountered, the author presents the accomplishments made through the education, experience, skills and capital which French Canadians have finally pooled together and put to productive use. At the corporate level, the most outstanding illustrations of this success are the National Bank of Canada, Provigo, The Laurentian Group and several large engineering, legal and chartered accountants' firms. We must not forget Bombardier which, from its humble beginnings as a snowmobile manufacturer, is now building subway trains and locomotives and will soon be building aircrafts.